Hubungan Motivasi Pasien dengan Kemampuan Mengontrol Resiko Kekambuhan Penyakit Jantung Koroner di RSUD Raden Mattaher Jambi - Bettywati E Tumanggor (Universitas Batanghari Jambi, 2020)
Coronary Heart Disease (CHD) is a non-contagious disease as the number one cause of death in the world. CHD in Indonesia becomes the highest pravency for cardiovascular disease. Primary, secondary and tertiary prevention is needed to control CHD risk factors. The purpose of this study to determine the correlation between motivation of patients with the ability to control the Risk of Coronary Heart Disease Recurrence at hospitals Raden Mattaher Jambi 2018. The design used in this study is quantitative research with cross sectional approach to take 84 people as a sample by purposive sampling. Research data were analyzed univariat and bivariate using chi square test with significance level p <0,05. The result showed that there was a significant correlation between motivation of patient with ability to control the risk of CHD Recurrence. Required the provision of health education related to the prevention of CHD to further improve understanding and improve the positive motivation of patients. Such as providing a special time to provide health education to patients and families, distributing leaflets, or showing special videos of CHD prevention that patients can see while waiting for a line at the heart polyclinic.